Selective MAP1LC3C (LC3C) autophagy requires noncanonical regulators and the C-terminal peptide - Bischoff, Megan E. (J Cell Biol, 2021)
LC3s are canonical proteins necessary for the formation of autophagosomes. We have previously established that two paralogs, LC3B and LC3C, have opposite activities in renal cancer, with LC3B playing an oncogenic role and LC3C a tumor-suppressing role. LC3C is an evolutionary late gene present only in higher primates and humans. Its most distinct feature is a C-terminal 20-amino acid peptide cleaved in the process of glycine 126 lipidation. Here, we investigated mechanisms of LC3C-selective autophagy. LC3C autophagy requires noncanonical upstream regulatory complexes that include ULK3, UVRAG, RUBCN, PIK3C2A, and a member of ESCRT, TSG101. We established that postdivision midbody rings (PDMBs) implicated in cancer stem-cell regulation are direct targets of LC3C autophagy. LC3C C-terminal peptide is necessary and sufficient to mediate LC3C-dependent selective degradation of PDMBs. This work establishes a new noncanonical human-specific selective autophagic program relevant to cancer stem cells.